Z-source matrix rectifier - Hongchen, Liu; Yuliang, Ji; Dan, Zhao; Wheeler, Patrick; Guolei, Fan (IET, 2016)
This paper presents a novel Z-source matrix rectifier(ZSMR). To overcome the inherent disadvantage that the voltage transfer ratio for traditional matrix rectifier cannot be more than 0.866, a Z-source network has been combined with the matrix rectifier. The proposed rectifier realizes a voltage-boost function and the Z-source network also serves as power storage and guarantees double filtration grade at the output of the rectifier. The open-circuit zero state is required to obtain the voltage-boost function and ensure the output angle of the current vector to be invariant to obtain the expected power factor. In addition, to widely extend the voltage transfer ratio of the proposed rectifier, this paper presents the switched-inductor matrix rectifier(SL-ZSMR) and tapped-inductor matrix rectifier(TL-ZSMR). The corresponding circuit topologies, control strategies and operating principles are introduced. Both simulation and experiment results are shown to verify the theoretical analysis.